2012
DOI: 10.1016/j.tranpol.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cost overruns for Dutch transport infrastructure projects and the importance of the decision to build and project phases

Abstract: Full reference: Cantarelli, C. C., Molin, E. J. E., van Wee, B., and Flyvbjerg, B. 2012.Characteristics of cost overruns for Dutch transport infrastructure projects and the importance of the decision to build and project phases. Transport Policy, 22: 49-56.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 12 publications
5
82
2
1
Order By: Relevance
“…A significant amount of past research in PPP projects for roadway construction and preservation has focused on the identification of factors affecting cost savings, cost overrun, time delays, and change orders (Rowland, 1981;Hester et al, 1991;Majid and McCaffer, 1998;Jacoby, 2001;Ellis and Thomas, 2003;Fimpong et al, 2003;Flyvbjerg et al, 2003;Bordat et al, 2004;Odeck, 2004;Assaf and Al-Hejji, 2006;Gkritza and Labi, 2008;Anastasopoulos et al, 2010aAnastasopoulos et al, ,b,c, 2011Anastasopoulos et al, , 2014Serag et al, 2010;Ambituuni, 2011;Irfan et al, 2011;Cantarelli et al, 2012). For example, Odeck (2004) formulated a regression framework to investigate the factors affecting cost overrun in roadway construction projects and found that small-scale projects are more vulnerable to cost overrun.…”
Section: Review Of Past Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant amount of past research in PPP projects for roadway construction and preservation has focused on the identification of factors affecting cost savings, cost overrun, time delays, and change orders (Rowland, 1981;Hester et al, 1991;Majid and McCaffer, 1998;Jacoby, 2001;Ellis and Thomas, 2003;Fimpong et al, 2003;Flyvbjerg et al, 2003;Bordat et al, 2004;Odeck, 2004;Assaf and Al-Hejji, 2006;Gkritza and Labi, 2008;Anastasopoulos et al, 2010aAnastasopoulos et al, ,b,c, 2011Anastasopoulos et al, , 2014Serag et al, 2010;Ambituuni, 2011;Irfan et al, 2011;Cantarelli et al, 2012). For example, Odeck (2004) formulated a regression framework to investigate the factors affecting cost overrun in roadway construction projects and found that small-scale projects are more vulnerable to cost overrun.…”
Section: Review Of Past Workmentioning
confidence: 99%
“…These studies identified the project duration as a major influential factor for the cost overrun or cost savings. Cost overrun was also examined with respect to the successive phases of the project development, with the stage between the decision for the project implementation and the beginning of the construction works being critical for the cost overrun (Cantarelli et al, 2012).…”
Section: Review Of Past Workmentioning
confidence: 99%
“…The relationship between project size and cost overruns is notable as the larger the construction project is greater in the percentage cost overrun. The factors that contribute cost overrun are price escalation, poor design and implementation, inadequate financial plans, administrative uncertainty and the lack of coordination between enterprises [18]. Apart from these factors mentioned, the completion time or the duration of the project will also play a vital role.…”
Section: Ascmces-17mentioning
confidence: 99%
“…Authors such as Martin et al (2006), EC Harris and TRL (2009), Flyvbjerg et al (2008), HS2 (2009, NAO (2012), Cantarelli et al (2010Cantarelli et al ( , 2012, Helm (2013) Madter and Bower (2015) and HM Treasury (2010 point toward increasing client and management costs, as well as a lack of skills and ability within ICOs. Indeed, the Infrastructure Cost Review (ICR) (HM Treasury, 2010) identified client leadership, overly complicated procurement practices and poor design specification as the top three areas for reducing costs.…”
Section: Infrastructure Client Organisationsmentioning
confidence: 99%